Nodular Epithelial Hyperplasia after Photorefractive Keratectomy Followed by Corneal Collagen Cross-Linking - Bogoni, Ayla (Hindawi Publishing Corporation, 2013)
This study describes a case of nodular epithelial hyperplasia and stromal alterations in a patient with keratoconus who was submitted to topography-guided photorefractive keratectomy (PRK) followed by corneal collagen cross-linking. Debridement of the epithelial nodule was performed. After a 2-year followup, a new topography-guided PRK was indicated.